Efeito do hidróxido de cálcio na formulação de cimentos resinosos autoadesivos - Madruga, Francine Cardozo (2012)
In this study the effect of the addition of calcium hydroxide Ca(OH)2 on the pHneutralization and physico-chemical properties of experimental self-adhesive resin cements was investigated. The cements were formulated as two pastes: Paste A, containing UDMA, Bis-GMA, TEGDMA, HEMA, GDMA-P and glass particles; Paste B, composed of UDMA, HEMA, water, photoinitiators and glass particles. The formulation variable tested was concentration of Ca(OH)2, added to paste B at mass fractions of 0% (control), 0.25%, 0.5%, 1%, 2%, and 4%. Equal volumes of pastes A and B were mixed for the analyses, which started by immersion of cement specimens in distilled water and follow up of the pH of the eluate for 24 h. The additional analyses consisted in measurement of degree of C=C conversion by infrared spectroscopy, film thickness, flexural strength, elastic modulus and work-of-fracturei n 3-point bending mode, Knoop hardness, depth of cure, water sorption and solubility after immersion in water for 7 days, and dentin bond strength by shear testing. Statistical comparisons between groups were carried out at a 5% significance level. All Ca(OH)2 concentrations above 0.25% caused pH increase of the eluate at 24 h, although the only concentrations of the compound leading to pH-neutralization were 2% and 4%. Compared with the control cement, the addition of 4% Ca(OH)2 decreased the flexural strength, flexural modulus, work-of-fracture, degree of C=C conversion, and dentin bond strength. In contrast, the physico-chemical properties of the material with 2% Ca(OH)2 were similar to the control material, except for a discreet reduction in mechanical strength and the lower film thickness of the material containing Ca(OH)2. Hardness, depth of cure, and water sorption were not affected by incorporation of Ca(OH)2. The material with 4% Ca(OH)2 had lower solubility and film thickness than the other cements. In conclusion, judicious incorporation of Ca(OH)2 might lead no pH-neutralization of self-adhesive resin cements without negatively interfering with other physico-chemical properties of the material.